2012
DOI: 10.3168/jds.2011-5107
|View full text |Cite
|
Sign up to set email alerts
|

Influence of starter protein content on growth of dairy calves in an enhanced early nutrition program

Abstract: Our objectives were to determine the effect of starter crude protein (CP) content on growth of Holstein calves from birth to 10 wk of age in an enhanced early nutrition program, and to compare the enhanced program to a conventional milk replacer program. Calves (64 female, 25 male) were assigned to 3 treatments in a randomized block design: 1) conventional milk replacer (20% CP, 20% fat) plus conventional starter [19.6% CP, dry matter (DM) basis], 2) enhanced milk replacer (28.5% CP, 15% fat) plus conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
78
6
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 25 publications
11
78
6
7
Order By: Relevance
“…An alternative to weaning by age, which is common in our industry, is the traditional concentrate-or starter-dependent weaning strategy. Optimal preweaning starter intake before step down (>0.5 kg/d) is essential for postweaning intake and gain and is influenced by the nutrient content of the milk replacer and calf starter (Stamey et al, 2012;Kertz and Loften, 2013). Greenwood et al (1997) demonstrated that calves fed low planes of nutrition could be successfully weaned when starter intake reaches 1% of BW.…”
mentioning
confidence: 99%
“…An alternative to weaning by age, which is common in our industry, is the traditional concentrate-or starter-dependent weaning strategy. Optimal preweaning starter intake before step down (>0.5 kg/d) is essential for postweaning intake and gain and is influenced by the nutrient content of the milk replacer and calf starter (Stamey et al, 2012;Kertz and Loften, 2013). Greenwood et al (1997) demonstrated that calves fed low planes of nutrition could be successfully weaned when starter intake reaches 1% of BW.…”
mentioning
confidence: 99%
“…Entretanto, o consumo aumenta quando o volume de leite fornecido é reduzido ou cessado (Stamey et al 2005, Hill et al 2006, sendo essa relação inversa entre o leite e o consumo de ração sólida (Khan et al 2007, Terré et al 2007, Raeth--Knight et al 2009 Os pesos absolutos do trato digestivo, ruminorretículo, omaso e dos intestinos foram influenciados pelo sistema de aleitamento, sendo verificadas médias superiores nos bezerros do sistema de aleitamento fracionado (Quadro 3).…”
Section: Resultsunclassified
“…Adotar o aleitamento acelerado inicialmente, com restrições gradativas até a desmama, pode permitir que os bezerros se alimentem com quantidades de leite mais pró-ximas das condições em que os bezerros teriam acesso ad libitum ao leite (Stamey et al 2005). O aleitamento em volumes crescentes nas primeiras semanas de vida, seguido pela redução gradual até o desaleitamento vem sendo indicado, pois o fornecimento de grande quantidade de leite, durante todo o período, resulta em menor consumo de concentrado nas fases iniciais, tendo, como consequência, menor desenvolvimento do rúmen ao desaleitamento (Davis & Drackley 1998).…”
Section: Introductionunclassified
“…Using this approach, milk feeding rates are almost double the traditional feeding rates, giving calves 1.5% of body weight as milk solids during the fi rst week of life, followed by 2% of body weight from week 2 until the week before weaning, when one liquid feeding per day is dropped (Stamey et al, 2005 ;Drackley, 2008 ). Compared to conventional milk replacer feeding programs, accelerated milk replacer feeding programs can deliver expected growth rates of 1.3 -1.8 lb/day (0.59 -0.82 kg/day), compared to 1.1 -1.3 lb/day (0.50 -0.59 kg/ day) for conventionally fed calves from days 0 to 42 (Drackley, 2008 ).…”
Section: Colostrummentioning
confidence: 99%